'Lines of Becoming' Misha Black and Entanglements through Exhibition Design. (12th December 2020) - Atkinson, Harriet
Abstract: In many historical accounts exhibitions are considered in isolation, in relation to specific political or cultural events. This article instead interrogates exhibitions as interlinked sites of personal and professional 'entanglement', connected entities that have capacity to sustain and develop multiple relationships, in this case across the career of a single designer, Misha Black (1910–1977). Through successive commissions, Black developed ideas about exhibitions as communication and propaganda, as well as developing his network and modelling formations for professional design practice. Exhibitions Black worked on which are discussed here included The Ibero-American Exhibition, Seville, 1929–1930; MARS Group Exhibition, 1938; Glasgow Empire Exhibition, 1938; New York World's Fair, 1939–1940; Ministry of Information exhibitions mounted during the Second World War and the Festival of Britain, 1951.